M26 Convergent validity of bronchiectasis quality of life tools in the BRONCH-UK registry. (12th November 2019) - Brown, J; Bradley, J; Copeland, F; Carroll, M; Crichton, M; Duckers, J; Haworth, C; Floto, RA; Hill, AT; Loebinger, M; Wilson, R; Hurst, J; et al.
Abstract : Introduction: Two quality of life instruments are widely used in bronchiectasis clinical trials, the Quality of Life bronchiectasis questionnaire and the St Georges Respiratory Questionnaire with few large scale multi-centre direct comparisons. Convergent validity represents an assessment of the instrument against other measures that are considered to represent severity of disease, since a valid instrument should agree with clinical assessments of severity of disease and disease burden. We evaluated the convergent validity in the BRONCH-UK dataset. Methods: Prospective registry of adults with bronchiectasis from 13 secondary care centres across the UK, embedded within the EMBARC European platform. Patients completed baseline QOL-B and SGRQ and comprehensive clinical assessment. Linear regression and Spearman correlation evaluated the relationship between QOL scores and clinical variables. Results: 1403 patients were recruited. We report data on the first 813 with complete core datasets; 504 were female (62%), 309 male (38%). The mean age 65 years SD 12.6. The mean QOL-B RSS was 61 points (SD 22) and mean SGRQ was 42.2 (SD 22) indicating a population with moderate to severe impairment of quality of life There was a strong inverse relationship between the QOL-B respiratory symptom score and the SGRQ (r=-0.74, p<0.0001). Similar relationships were observed across all domains. The QOL-B RSS correlated with FEV1% predicted (r=0.31, p<0.0001), MRC dyspnoea score (r=-0.47, p<0.0001), daily sputum volume (r=-0.46, p<0.0001), exacerbation frequency (r=-0.24, p<0.0001) and the bronchiectasis severity index (r=-0.35, p<0.0001). The SGRQ was correlated with FEV1% predicted (r=-0.32, p<0.0001), MRC dyspnoea score (r=0.55, p<0.0001), daily sputum volume (r=0.42, p<0.0001), exacerbation frequency (r=0.29, p<0.0001) and the BSI (r=0.39, p<0.0001). High risk populations e.g. chronic P. aeruginosa infection and frequent exacerbators (3 or more per year) had higher SGRQ and lower QOL-B RSS scores (p<0.0001 for all comparisons). Conclusion: Both the QOL-B RSS and the St Georges Respiratory Questionnaire show acceptable convergent validity in large representative population of patients with bronchiectasis in the UK. Acknowledgements: MRC Funding grant MR/L011263/1, Recruiting sites and patients